From Sarawak to The World: One Sustainable Spoon at a Time - Hung Moi, Tang (International Digital Economy Conference Sarawak 2025 (IDECS 2025), 2025)
Borsa Food Sdn Bhd is a Sarawak-born sustainable food manufacturer and distributor producing nutritious functional foods for a low-carbon future. The poster introduces two house brands: YourgutBB Kuching, offering probiotic, low-sugar, gut-friendly products made fresh daily from real ingredients; and NaVe, a purely plant-based range. Highlighted products include natural frozen yogurt, authentic Greek yogurt, stirred yogurt and Greek Yogurt Powerbite, with other offerings such as almond milk, konjac jelly and fruit jam too. The business is designed around circular economy principles: local labour and locally sourced ingredients support manufacturing, while waste management focuses on composting organic waste, segregating recyclables, and minimising landfill disposal. On the consumption side, the system emphasises low energy use, zero-waste practices, low-carbon operations, circular packaging, and freshly made-on-demand products. Customers are encouraged to return, refill, regenerate, reuse, upcycle, and repeat through ongoing education.